Incidencia de la gestión administrativa en la rentabilidad de la empresa comisariato escolar de la Ciudad de Babahoyo, Periodo 2014 – 2015. - Parrales Carvajal, Víctor Martín (2016)
In a world so competitive them companies and organizations is come in the need of adapt is to them new changes and to the new form of innovate, operate in an environment in which are interrelated with their customers, suppliers among others. Many managers, shareholders or owners of commercial establishments are unaware of the administrative management or do not want them to apply because without it their business has grown through the years and have increased their sales, without even imagining that in the not too distant future it will be useful and necessary to achieve excellence in the administrative management of the company. The present research work aims to analyze the impact of the administrative management in the profitability of the curatorial School of the city of Babahoyo, in order to detect problems by a possible incorrect financial and administrative management and propose viable alternatives to improve them if it were the case, the result shall be a set of tools that will support and guide the company , allowing achieving the achievement of their objectives and goals. Was inescapable identify them procedures of management administrative and financial that currently is developing it company to achieve to the target main of the present research; also analyzed how incurs the human ratio to achieve the purpose that the company wants to, also analyzed the profitability of the company commissary school in order to improve their income for the benefit of the company, management and staff working in the institution. Of the issues raised, will be optimize administrative management and profitability of the company to establish strategies involving objectives to strengthen the administrative processes of the curatorial School of the city of Babahoyo